2000
DOI: 10.1258/1357633001935347
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of telemedicine for orthopaedic outpatient clinicsa randomized controlled trial

Abstract: We investigated the use of videoconferencing in the examination of orthopaedic outpatients. A consecutive sample of orthopaedic outpatients was randomized to examination either via videoconferencing (n = 76) while attending a primary-care unit or at a conventional hospital outpatient clinic 160 km away (n = 69). Videoconferencing was found to be feasible and the equipment functioned well technically. There were somewhat more problems in examining the telemedicine patients than the clinic patients. The two pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 13 publications
3
101
0
1
Order By: Relevance
“…In 1999, the first e-referral services between electronic patient record (EPR) systems at the university hospital and primary care centres in the region were started (7). This supplements the current network of e-consultation tools, such as teleradiology, videoconsultation services in surgery and psychiatry, and elearning opportunities for professionals (8,9).…”
Section: Electronic Communication Between Primary and Secondary Carementioning
confidence: 79%
“…In 1999, the first e-referral services between electronic patient record (EPR) systems at the university hospital and primary care centres in the region were started (7). This supplements the current network of e-consultation tools, such as teleradiology, videoconsultation services in surgery and psychiatry, and elearning opportunities for professionals (8,9).…”
Section: Electronic Communication Between Primary and Secondary Carementioning
confidence: 79%
“…a GP, a general surgeon or a resident) have been present at the remote site together with the patient [8,10,11,34,35]. Some studies reported that a nurse present at the remote site and a specialist at the hospital could provide satisfactory remote consultations in emergency medicine [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the use of telemedicine to facilitate treatment and care over distance has been investigated in almost all clinical specialties [5][6][7]. Several studies have demonstrated the feasibility of using telemedicine to provide orthopaedic consultations to patients living in remote areas [8][9][10][11]. Teleorthopaedics involve the delivery of specialist services across a distance, usually between an orthopaedic surgeon and a patient [12].…”
Section: Introductionmentioning
confidence: 99%
“…32 Accordingly, some surgeons have removed "hands-on" assessments, conducting perioperative visits using secure two-way interactive video. [33][34][35][36][37] Still others have eliminated both "hands-on" and visual assessments, using telephone to follow-up adults after laparoscopic cholecystectomy and inguinal hernia repair as well as a variety of minor pediatric general surgical procedures. [38][39][40] Both video and telephone-based care are limited in that they must be performed in a synchronous fashion, with both patient and surgeon available concurrently to participate in follow-up.…”
Section: Discussionmentioning
confidence: 99%